Cultivating Students' Aesthetic Taste While Looking at the Works of World Composers in Music Lessons - Alekseyevna, Alexandrova Olga (International Journal on Orange Technologies, 2023)
In the article, a theoretical analysis of the formation of the aesthetic taste of the students, education and improvement of their knowledge through the works of world classical composers in the music classes is made. The positive influence of classical music on the education of students is covered in depth.